Tolerability of four‐drug antiretroviral combination therapy in primary HIV‐1 infection. Issue 8 (8th May 2021) - Burns, JE; Stöhr, W; Kinloch‐De Loes, S; Fox, J; Clarke, A; Nelson, M; Thornhill, J; Babiker, A; Frater, J; Pett, SL; Fidler, S
Abstract : Objectives: Rapid initiation of antiretroviral therapy (ART) is important for individuals with high baseline viral loads, such as in primary HIV‐1 infection (PHI). Four‐drug regimens are sometimes considered; however, data are lacking on tolerability. We aimed to evaluate the tolerability of four‐drug regimens used in the Research in Viral Eradication of HIV‐1 Reservoirs (RIVER) study. Methods: At enrolment, ART‐naïve adult participants or those newly commenced on ART were initiated or intensified to four‐drug regimens within 4 weeks of PHI. Rapid start was defined as pre‐confirmation or ≤ 7 days of confirmed diagnosis. Primary and secondary outcomes were patient‐reported adherence measured by 7‐day recall and regimen switches between enrolment and randomization, respectively. Results: Overall, 54 men were included: 72.2% were of white ethnicity, with a median age of 32 years old, 42.6% had a viral load of ≥ 100 000 HIV‐1 RNA copies/mL, and in 92.6% sex with men was the mode of acquisition of HIV‐1. Twenty (37%) started a four‐drug regimen and 34 (63%) were intensified. Rapid ART initiation occurred in 28%, 100% started in ≤ 4 weeks. By weeks 4, 12, and 24, 37.0%, 69.0%, and 94.0% were undetectable (viral load < 50 copies/mL), respectively. Adherence rates of 100% at weeks 4, 12, 22 and 24 were reported in 88.9%, 87.0%, 82.4% and 94.1% of participants, respectively. Five individuals switched to three drugs, four changed their regimen constituents, and two switched post‐randomization. Conclusions: Overall, four‐drug regimens were well tolerated and had high levels of adherence. Whilst their benefit over three‐drug regimens is lacking, our findings should provide reassurance if a temporarily intensified regimen is clinically indicated to help facilitate treatment.